Determination of temperature dependences of material constants for lead-free (Na0.5K0.5)NbO3–Ba2NaNb5O15 piezoceramics by inverse method - Yoshida, Katsuya; Kakimoto, Kenichi; Weiß, Manuel; Rupitsch, Stefan; Lerch, Reinhard (Japanese Journal of Applied Physics, 2016)
The enhancement of the piezoelectric, dielectric, and elastic properties of lead-free piezoceramics is essential to achieving a usable alternative to common lead-based piezoceramics. In this contribution, the temperature dependences of the material constants for 0.985(Na0.5K0.5)-NbO3–0.015Ba2NaNb5O15 (NKN–1.5BNN) were characterized and compared with those of MnO-doped (Na0.5K0.5)NbO3 (NKN–Mn). The material constants were determined by the simulation-based inverse method. As a result, NKN–Mn and NKN–1.5BNN were found to show significant differences in the temperature behaviors of piezoelectric, elastic, and dielectric constants. In particular, for temperatures less than 40 °C, material constants that mainly affect shear mode vibration in NKN–1.5BNN gradually increased with increasing temperature, whereas those of NKN–Mn remained constant because of a different crystal structure. In addition, we explain the observed mechanical softness of NKN–1.5BNN in the shear direction on the basis of characteristic material constant relations, macroscopic (scanning electron microscopy), and crystal structure examinations (X-ray diffractometry).

Determination of temperature dependency of material parameters for lead-free alkali niobate piezoceramics by the inverse method - Ogo, Kenji; Kakimoto, Kenichi; Weiß, Manuel; Rupitsch, Stefan; Lerch, Reinhard (AIP Advances, 2016)
Sodium potassium niobate (NKN) piezoceramics have been paid much attention as lead-free piezoelectric materials in high temperature devices because of their high Curie temperature. The temperature dependency of their material parameters, however, has not been determined in detail up to now. For this purpose, we exploit the so-called Inverse Method denoting a simulation-based characterization approach. Compared with other characterization methods, the Inverse Method requires only one sample shape of the piezoceramic material and has further decisive advantages. The identification of material parameters showed that NKN is mechanically softer in shear direction compared with lead zirconate titanate (PZT) at room temperature. The temperature dependency of the material parameters of NKN was evaluated in the temperature range from 30 °C to 150 °C. As a result, we figured out that dielectric constants and piezoelectric constants show a monotonous and isotropic increment with increasing temperature. On the other hand, elastic stiffness constant of NKN significantly decreased in contrast to other elastic stiffness constants. It could be revealed that the decrement of <span class="MathJax" data-mathml="<msubsup>c44E</msubsup>" id="MathJax-Element-5-Frame" role="presentation" style="position: relative;" tabindex="0">cE44 is associated with an orthorhombic-tetragonal phase transition. Furthermore, ratio of elastic compliance constants exhibited similar temperature dependent behavior to the ratio of piezoelectric constants d 15/d 33. It is suspected that mechanical softness in shear direction is one origin of the large piezoelectric shear mode of NKN. Our results show that NKN are suitable for high temperature devices, and that the Inverse Method should be a helpful approach to characterize material parameters under their practical operating conditions for NKN.

Material constants of alkali niobate lead-free piezoceramics determined by the Inverse Method - Ogo, Kenji; Kakimoto, Kenichi; Weiß, Manuel; Rupitsch, Stefan; Lerch, Reinhard (The Ceramic Society of Japan, The 28th Fall Meeting, 2015)

Nb2AlC-particle induced accelerated crack healing in ZrO2–matrix composites - Stumpf, Martin; Fey, Tobias; Kakimoto, Kenichi; Greil, Peter (Ceramics International, 2018)
The oxidation induced crack healing behavior of pre-cracked Nb2AlC particle loaded ZrO2-matrix composites was explored by annealing in air at 1200 °C for short periods of 10 and 20 min. Composites loaded with 0, 6.5, 13, and 19.5 vol. % Nb2AlC powder dispersed in 3Y-TZP matrix powder were manufactured by spark plasma sintering (SPS) at 1300 °C. Semi-elliptical artificial surface cracks with a length exceeding 220 µm were produced by Vickers indentation. The modulus of rupture of virgin, indented and annealed samples was measured in three-point bending mode. Compared to single phase 3Y-TZP strength recovery of the Nb2AlC loaded composite upon annealing at 1200 °C in air is accelerated and reaches > 60% of the initial strength after a short healing period of 10 min only. A semi-empirical oxidation cohesive zone healing model was derived which describes the crack microstructure evolution as a combined effect of 3Y-TZP-matrix healing superimposed by Nb2AlC particle oxidation induced healing.<br
Keywords: Crack healing; Nb2AlC particle inclusion; ZrO2-based composites